The impact of pulmonary metastasectomy from gastric cancer - Oguri, Yohei (Mol Clin Oncol, 2019)
Gastric cancer remains the most commonly-occurring cancer and the third most frequent cause of cancer-associated mortality in Japan. Solitary pulmonary metastasis of gastric cancer is rare and the outcome of pulmonary metastasectomy is still unclear. Herein we report the impact of pulmonary resection in patients with metastasis from gastric cancer. The present study retrospectively reviewed the preoperative data and clinical courses of 10 patients who underwent pulmonary resection for metastasis from gastric cancer at our institution between July 1986 and December 2017. The data on the outcomes, including morbidity, mortality and survival, were obtained from the patient records. All patients were followed-up from the time of pulmonary resection until mortality or referral to another hospital. The statistical analyses were performed using EZR (Saitama Medical Center, Jichi Medical University, Saitama, Japan), which is a graphical user interface for the R software program (The R Foundation for Statistical Computing, Vienna, Austria). The study population included 7 male patients and 3 female patients. A total of 5 patients underwent total gastrectomy, and 5 underwent distal gastrectomy. The median disease-free interval after initial gastric resection was 34.5 months. Five patients received adjuvant chemotherapy, of the 10 thoracotomies, 5 were lobectomy, 3 were wedge resection and 2 were segmentectomy. The median overall survival following pulmonary metastasectomy was 59 months and the 5-year survival rate was 40.5%. Taken together, the results of the present study suggest that pulmonary resection may be an effective therapeutic option for metastatic gastric cancer when a patient has a solitary metastatic lesion.